2018
DOI: 10.3746/pnf.2018.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Insulinotropic Effect of S-Allyl Cysteine in Rat Pups

Abstract: S-Allyl cysteine (SAC) is found in garlic and has been reported to exert antidiabetic and antiobesity properties in drug-induced adult experimental models of metabolic dysfunction, but its potential beneficial effects in high-fructose diet neonatal rat models have not been determined. This study investigated the potential prophylactic effects of SAC in high-fructose diet fed suckling rat pups modelling human neonates fed a high-fructose diet. Four-day-old male (n=32) and female (n=32) Wistar rat pups, were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Currently, we do not have an explanation for the sexual dimorphic effect of zingerone on SREBP1c expression; thus, further investigation is required. Nonetheless, preceding studies have reported that sexual dimorphism in rats can be attributed to variance in rate and pattern of early development and responses to insult in male and female rats [ 55 , 56 ]. In vivo zingerone activates PPAR-α [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we do not have an explanation for the sexual dimorphic effect of zingerone on SREBP1c expression; thus, further investigation is required. Nonetheless, preceding studies have reported that sexual dimorphism in rats can be attributed to variance in rate and pattern of early development and responses to insult in male and female rats [ 55 , 56 ]. In vivo zingerone activates PPAR-α [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…S-allyl cysteine, administered during the neonatal period for 15 days in rats, did not alter insulin levels 97 . Another study by the same investigators reported that s-allyl-cysteine produced an insulinotropic effect immediately after the weaning period in the absence of a second hit of fructose insult 98 , thus demonstrating a time-bound effect of s-allyl-cysteine. The time-bound effect could also explain the increased glucose levels observed in the offspring of HFD-fed dams upon weaning in response to resveratrol intake 96 .…”
Section: Beneficial Effects Of Phytochemicals and Plant Extracts Agai...mentioning
confidence: 92%